2005
DOI: 10.1021/la047398n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Degassing and Ionic Strength on AFM Force Measurements in Octadecyltrimethylammonium Chloride Solutions

Abstract: Sakamoto et al. (Langmuir 2002, 18, 5713) conducted AFM force measurements between silica sphere and fused-silica plate in aqueous octadecyltrimethylammonium chloride (C18TACl) solutions and concluded that long-range attractive force is not observed in carefully degassed solutions. In the present work, AFM force measurements were conducted by following the procedures described by Sakamoto et al. The results showed the presence of an attractive force that was much stronger than the van der Waals force both in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 46 publications
10
72
0
Order By: Relevance
“…According to Fuerstenau and Pradip (2005), hemi-micelles begin to form at concentrations 2-3 orders of magnitude below the c.m.c. The AFM (Zhang et al, 2005) and SEM (Delamarche, et al, 1994) images of the surfactant-coated surfaces indeed showed patches, as is also shown in Figure 15. Further, the aggregation numbers of the hemi-micelles (or 'soloids') determined using the electron spin resonance (ESR) and fluorescence spectroscopic techniques showed the patch-wise adsorption mechanism (Fan et al, 1997;Ström et al, 2000).…”
Section: Possible Origin(s) Of Hydrophobic Forcesupporting
confidence: 62%
“…According to Fuerstenau and Pradip (2005), hemi-micelles begin to form at concentrations 2-3 orders of magnitude below the c.m.c. The AFM (Zhang et al, 2005) and SEM (Delamarche, et al, 1994) images of the surfactant-coated surfaces indeed showed patches, as is also shown in Figure 15. Further, the aggregation numbers of the hemi-micelles (or 'soloids') determined using the electron spin resonance (ESR) and fluorescence spectroscopic techniques showed the patch-wise adsorption mechanism (Fan et al, 1997;Ström et al, 2000).…”
Section: Possible Origin(s) Of Hydrophobic Forcesupporting
confidence: 62%
“…This is a mean field (MF) theory, within which ions are treated as point-like particles obeying a Boltzmann distribution, the aqueous solution is taken as a continuous and homogeneous dielectric medium, and in most treated cases , the bounding surfaces are assumed to be homogeneously charged [1][2][3][4][5][6]. However, as many charged surfaces in soft and biological matter are heterogeneous over mesoscopic length scales, several experimental [7][8][9][10][11][12][13][14][15][16] and theoretical studies have investigated the effects of surfacecharge heterogeneity on the inter-surface electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have examined the interaction between two such overall neutral surfaces, made of positive and negative domains ("patches") that are much larger than the molecular size [7][8][9][10][11][12][13][14]. For example, negative mica surfaces can be coated with neutralizing cationic surfactants that later dissociate and form positively charged bilayer patches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown also that the long-range attractions disappeared when the force measurements were conducted in degassed solutions (10). Follow-up experiments showed, however, that strong hydrophobic force can still be measured between silica surfaces immersed in degassed cetyltrimethylammonium bromide (CTAB) solutions (13). The force curves obtained between hexadecanethiol (C 16 SH)-coated gold surfaces also showed steps and showed no significant hydrophobic force (14).…”
Section: Introductionmentioning
confidence: 99%